2019
DOI: 10.1098/rspb.2019.0364
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal flight-calling behaviour predicts vulnerability to artificial light in migratory birds

Abstract: Understanding interactions between biota and the built environment is increasingly important as human modification of the landscape expands in extent and intensity. For migratory birds, collisions with lighted structures are a major cause of mortality, but the mechanisms behind these collisions are poorly understood. Using 40 years of collision records of passerine birds, we investigated the importance of species' behavioural ecologies in predicting rates of building collisions during nocturnal migration throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 47 publications
6
77
0
Order By: Relevance
“…This experiment convincingly demonstrated an impact of road noise (rather than the road itself) on the usage of a migratory stop-over site. However, for both of the aforementioned field playback studies different mechanisms could have been underlying the reductions in birds attending the sites: the noise itself could have kept the birds away and/or the noise masked the vocalizations of the birds already on site and thereby prevented the phonotactic aggregation of more birds (Mönkkönen & Forsman, 2002;Winger et al, 2019), a phenomenon that has been demonstrated experimentally (Schepers & Proppe, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This experiment convincingly demonstrated an impact of road noise (rather than the road itself) on the usage of a migratory stop-over site. However, for both of the aforementioned field playback studies different mechanisms could have been underlying the reductions in birds attending the sites: the noise itself could have kept the birds away and/or the noise masked the vocalizations of the birds already on site and thereby prevented the phonotactic aggregation of more birds (Mönkkönen & Forsman, 2002;Winger et al, 2019), a phenomenon that has been demonstrated experimentally (Schepers & Proppe, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Our model could also give mechanistic insight into why birds fly toward and crash into artificial light sources at night. These sources, which can be lighthouses (40), monuments (41), or skyscrapers (42), are estimated to lead to billions of bird deaths a year (43). Steady lights-like the one in our study-can be particularly attractive and thus disorienting for migrating birds (44).…”
Section: Neck Angle Gives Effective Gust Feedback and Scales Favorablmentioning
confidence: 89%
“…Building collisions are the second leading source of direct, human-caused bird mortality in North America, and are estimated to cause between 365-988 million deaths annually in the US [1] and between 16-42 million deaths annually in Canada [2]. Birds are attracted to lighted structures at night [3] or attempt to fly through windows in the daytime [4], only to collide and die upon impact or from injuries later on. Migratory species are especially at risk; the majority of collisions occur during migration, particularly in areas with strong levels of artificial light [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Birds are attracted to lighted structures at night [3] or attempt to fly through windows in the daytime [4], only to collide and die upon impact or from injuries later on. Migratory species are especially at risk; the majority of collisions occur during migration, particularly in areas with strong levels of artificial light [3,5].…”
Section: Introductionmentioning
confidence: 99%